Liberalisation policy: Implications for higher education - Haragopal, G.; Sudarshanam, G. (1996)
Critical of extending liberalisation policy to the field of higher education in India, the authors examine its basic postulates and their contextual validity and, drawing support from our experience in 60s and 70s, highlight the serious problems confronting our system today and their causes. Then, looking at the present centres of excellence - IIT's and IIMs - they point to their irrelevance as reflected in improper orientation and indifference of their products to our problems. Critical of Private Universities Bill, 1995, due to its de-emphasis on higher education, spread of `capitation fee', method of funding, etc., they conclude with a warning against grim situation resulting directly from liberalisation in this field in future. - Reproduced
Keywords: Liberalization - India; Education, Higher - India; Education; Educational planning